ANALISIS PERSPEKTIF INDONESIA PASCA PANDEMI COVID 19 - Adriani Adnani (Normative Jurnal Ilmiah Hukum, 2021)
Indonesia is the fourth most populous country in the world. To learn from experience, Indonesia desperately needs policies to be implemented in an emergency. Indonesian government need to focus on a policy response that aims to provide brief reporting, analysis and evaluation of the most recent rapid response to COVID-19 in Indonesia. For this reason, a perspective analysis is needed to provide insights and lessons for all stakeholders to improve and adjust existing policy options, especially at the national level from May 2020 to the end of the future crisis. Governments at various levels can prepare and manage their crisis and risk communication strategies by anticipating not only excess information on social media but also creating systems for minimizing victims. Transparency is key to managing a pandemic as it provides conditions in which infected people can be quickly identified and treated in a timely manner. National and local governments should develop integrated crisis and risk communication strategies that allow people to be informed to minimize people's irrational behavior. It is also important to build the capacity of high-level officials in local level government in decision-making and crisis communication during crisis situations